Alcohol Outlet Densities and Alcohol Price: The British Columbia Experiment in the Partial Privatization of Alcohol Sales Off‐Premise. (14th January 2013) - Treno, Andrew J.; Ponicki, William R.; Stockwell, Tim; Macdonald, Scott; Gruenewald, Paul J.; Zhao, Jinhui; Martin, Gina; Greer, Alissa
Abstract : Background: Alcohol beverage prices or taxes have been shown to be related to alcohol sales and use and related problems. What is not clear are the mechanisms underlying these relationships. Methods: This study examines the relationship between alcohol outlet density under conditions of the partial privatization of off‐premise consumption in British Columbia (BC) occurring over the past decade. Two hypotheses are tested. First, reflecting basic supply–demand principles, greater geographic densities of alcohol outlets will be directly related to reductions in beverage prices in response to greater competition. Second, reflecting the effects of niche marketing and resulting market stratification, increased densities of private liquor stores will be especially related to reductions in beverage prices within this outlet category. Data were collected from: (i) a survey of BC private store prices and practices, (ii) alcohol outlet location information, and (iii) data on demographic characteristics. Multilevel models examine the relationships between prices at individual private liquor stores and the densities of government liquor stores, private liquor stores, bars, and restaurants, controlling for background demographics and geographic unit level effects. Spatial dependencies were also examined. Results: Increased densities of private liquor stores were associated with lower mean prices of beer and all alcohol aggregated across brands at the store level. There appeared to be no outlet level effect on discounting patterns, however, with the mean price differences apparently reflecting differences in the quality of brands carried rather than unequal prices for any given brand. Conclusions: Increased densities of private off‐sale alcohol outlets appear to result in lower prices charged at said establishments independently of other types of alcohol outlets suggesting that they represent an emerging marketing niche in the context of off‐sale outlet privatization.